Analysis of Biofilm Adhesion on CAD/CAM Lithium Disilicates Under Different Types of Intraoral Polishing - Catanoze, Isabela A. [UNESP]; Souza, Heloisa S. de; Araujo, Renan C.; Limirio, Joao Pedro J. D. O.; Duque, Cristiane; Santos, Paulo H. dos; Pesqueira, Aldieris A.; Guiotti, Aimee M. (Dennis Barber Ltd, 2021)
Purpose: To evaluate the adhesion of Streptococcus mutans (S. mutans) on lithium disilicate ceramics, submitted to different intraoral polishing protocols, and the degree of surface smoothness obtained. Materials and Methods: Fifty lithium disilicate specimens were divided into 5 groups (n=10): G1-Glaze Group (positive control); G2-Glaze Group + Wear + Glaze; G3-Wear Group (negative control); G4-Ceramiste Wear Group; G5-Optrafine Wear Group. Surface roughness (Ra -mu m) was evaluated and the surface characteristics were assessed using a scanning electron microscope (SEM); to assess S. mutans biofilm, the number of cultured cells was evaluated by counting colony-forming units (CFU/mL). The data underwent one-way ANOVA followed by Tukey's test (P<.05). Results: There was a significant difference in the surface roughness of all groups compared with G3. There was no significant difference between the G4 and G5 groups that received polishing. G1 group had the lowest mean roughness values. There was a difference in Log values (CFU/mL) between the G3 group and the groups that received glaze (G1 and G2). The G3 group had the highest adhesion of S. mutans (4.53 Log). Conclusion: The most effective polishing protocol after wear is glazing, presenting the lowest roughness and CFU/mL values.
Keywords: Ceramics; Biofilms; Dental Polishing; Roughness Surface